Research on Modification of Oxygen-Producing Adsorbents for High-Altitude and Low-Pressure Environments - Ye Li; Huiqing Yue; Quanli Zhang; Dumin Yan; Ziyi Li; Zhiwei Liu; Yingshu Liu; Yongyan Wang; Shifeng Wang; Xiong Yang (Inorganics)
In oxygen production on plateaus, pressure swing adsorption (PSA) oxygen production is currently the most commonly used oxygen production method. In plateau regions, low pressure leads to a decrease in adsorbent nitrogen–oxygen separation performance, which affects the performance of PSA oxygen production, so it is particularly important to enhance adsorbent nitrogen–oxygen separation performance. In this paper, Li-LSX (lithium low-silicon aluminum X zeolite molecular sieve) adsorbents were modified using the liquid phase ion exchange method, and five kinds of modified adsorbents were obtained, namely AgLi-LSX, CaLi-LSX, ZnLi-LSX, CuLi-LSX, and FeLi-LSX, respectively. The influences of different metal ions and modification time lengths on the adsorbent nitrogen adsorption and nitrogen–oxygen separation coefficients were analyzed. Through theoretical calculations, the nitrogen and oxygen adsorption and separation performances of the modified adsorbents at different altitudes and low adsorption pressures were investigated. It is shown that the nitrogen adsorption capacity of the AgLi-LSX-1 adsorbent obtained from the modification experiment reaches 27.92 mL/g, which is 3.24 mL/g higher than that of Li-LSX; the nitrogen–oxygen separation coefficients of S1 and S2 are 19.24 and 7.54 higher, respectively; and the nitrogen–oxygen separation coefficients of S4 are 20.85 and 7.54 higher than those of Li-LSX, respectively. With the increase in altitude from 50 m to 5000 m, the nitrogen–oxygen separation coefficient of the AgLi-LSX-1 adsorbent increased rapidly from 20.85 to 57, and its nitrogen–oxygen separation coefficient S4 exceeded that of the Li-LSX adsorbent to reach 47.61 at an altitude of 4000 m. Therefore, the modified adsorbent AgLi-LSX-1 in this paper can enhance the performance of the PSA oxygen process for oxygen production in plateau applications.